Oral capillaroscopy: a new diagnostic method - F. Carini; G.A. Scardina; P. Messina (PAGEPress Publications, 2011)
The morphological-functional study of microcirculation is of fundamental importance; in fact, the microvascular bed is directly involved both in autoimmune etiopathogenesis pathologies, and in acute and chronic inflammatory etiopathogenesis pathologies. Oral capillaroscopy is a very stimulating method for studying microcirculation, because of the possibility of studying small vessels in vivo by means of a microscope. Today, it is becoming more reliable thanks to the improvement of the observation tools (photography, videomicroscopy).